If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 1 = 6 + 1 Reorder the terms: 1 + 6x = 6 + 1 Combine like terms: 6 + 1 = 7 1 + 6x = 7 Solving 1 + 6x = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 6x = 7 + -1 Combine like terms: 1 + -1 = 0 0 + 6x = 7 + -1 6x = 7 + -1 Combine like terms: 7 + -1 = 6 6x = 6 Divide each side by '6'. x = 1 Simplifying x = 1
| 9x+7=9x-4 | | 5x-4+5x=24 | | 3x+7x=9x-1 | | 4m+3=48 | | 3n-8n=-(6n+7)+3(-5+4n) | | -2(4w-x)+6(-5x-6w)= | | 7(3p-5)=7(3p-1) | | -3x-2(2y-3x)+5y= | | 5(x+6)+2=7x-8 | | 8t-21=9+4t | | -4w-3(-5x+6w)-3x= | | (-i+1)(3-2i)(1+3i)=0 | | 5x^2+2y^2+4xy-2x+4y+5=0 | | -19(8a+3b)= | | 3(3w+4)-12w= | | B^2-4bg-60g^2=0 | | 3(x+15)=9(2+x) | | -2(u+1)-6= | | (2+3i)(5-6i)=0 | | 4(4y-2)+2(2y+2)= | | (3/4)X(3/4)X(3/4)X(3/4)X(3/4) | | [6v-15]=[4v+7] | | F(x)=x^3-13x^2-30x | | -3(x+6)+x= | | =9m | | Y-28=-4y+3 | | 2(1.5x-5)x=2 | | 8a=63 | | 2(1.5-5)+x=2 | | 0.75-0.50n=0.625 | | 7[9-(-9x-4)]=504x+287 | | -48/-4 |